1993
DOI: 10.1111/j.1559-1816.1993.tb01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Model of Mammography Intention1

Abstract: This paper presents the results of a study testing components of the Triandis model of choice to predict intention to obtain screening mammography in the next 2 years. A questionnaire was developed to measure the theoretical components of this model. Analysis was based on 2,521 women, 50 to 65 years old, who received primary care from 1 of 28 participating primary care group practices. Based on the four theoretical components of intention described in the Triandis model‐social influence, affect, consequence, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 35 publications
0
8
1
1
Order By: Relevance
“…In addition, subjective norm did not have a direct influence on intention, as argued by the TRA, but was mediated by perceived barriers (Hypothesis 3). This finding contrasts with previous studies that reported a positive association between subjective norm and intention when controlling for attitudes (i.e., benefits and barriers) (7, 3942). This may be due to different measures of subjective norm.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, subjective norm did not have a direct influence on intention, as argued by the TRA, but was mediated by perceived barriers (Hypothesis 3). This finding contrasts with previous studies that reported a positive association between subjective norm and intention when controlling for attitudes (i.e., benefits and barriers) (7, 3942). This may be due to different measures of subjective norm.…”
Section: Discussioncontrasting
confidence: 99%
“…Baumann et al . point out that a simple weighted sum rule may represent a more rational model than typically occurs in human decision making 12 . In the literature, the application of variables in behavioural intention models and their exploration as response modifiers is varied 8 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that intention is more subject to be influenced by significant others when a behaviour is not well-incorporated into one's repertoire (Baumann, Brown, Fontana, & Cameron, 1993). Furthermore, a lack of personal experience would lead individual to rely more on views of significant others in performing a behaviour (Baumann et al, 1993). Therefore, participants who had no prior experiences in disclosing HIV status would value the views of others in disclosing HIV status.…”
Section: Discussionmentioning
confidence: 99%
“…The findings that descriptive and injunctive norms were significant factors to HIV disclosure intention were consistent with previous studies, which reported the positive influence of significant others on the intention to disclose. It has been suggested that intention is more subject to be influenced by significant others when a behaviour is not well‐incorporated into one's repertoire (Baumann, Brown, Fontana, & Cameron, ). Furthermore, a lack of personal experience would lead individual to rely more on views of significant others in performing a behaviour (Baumann et al, ).…”
Section: Discussionmentioning
confidence: 99%